Phase-Based Data Placement Scheme for Heterogeneous Memory Systems - Laghari, Mohammad; Ahmad, Najeeb; Unat, Didem (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
Heterogeneous memory systems are equipped with two or more types of memories, which work in tandem to complement the capabilities of each other. The multiple memories can vary in latency, bandwidth and capacity characteristics across systems and they come in various configurations that can be managed by the programmer. This introduces an added programming complexity for the programmer. In this paper, we present a dynamic phase-based data placement scheme to assist the programmer in making decisions about program object allocations. We devise a cost model to assess the benefit of having an object in one type of memory over the other and apply the cost model at every application phase to capture the dynamic behaviour of an application. Our cost model takes into account the reference counts of objects and incurred transfer overhead when making a suggestion. In addition, objects can be transferred across memories asynchronously between phases to mask some of the transfer overhead. We test our cost model with a diverse set of applications from NAS Parallel and Rodinia benchmarks and perform experiments on Intel KNL, which is equipped with a high bandwidth memory (MCDRAM) and a high capacity memory (DDR). Our dynamic phase-based data placement performs better than initial placement and achieves comparable or better performance than cache mode of MCDRAM.